The Impact Of Inflation And Bank Indonesia Exchange Rate On Stock Prices Of PT Goodyear Indonesia Tbk For The Period 2015-2024 - Anggriana, Dina; Sutiman, Sutiman (Universitas Dehasen Bengkulu, 2025)
This research aims to analyze the influence of inflation and Bank Indonesia's exchange rate on the stock price of PT Goodyear Indonesia Tbk during the period 2015-2024. The research methodology employed is descriptive quantitative. Secondary data were obtained from the company's annual reports, Bank Indonesia, the Central Statistics Agency (BPS), and the Indonesia Stock Exchange. Data analysis techniques utilized descriptive statistics, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination analysis using SPSS version 27. The research findings indicate that partially, inflation has a positive and significant effect on stock prices with a calculated t-value of 4.348 > t-table 2.44691 and significance of 0.003 < 0.05. Bank Indonesia's exchange rate has a negative and significant effect with a calculated t-value of -3.549 > t-table 2.44691 and significance of 0.009 < 0.05, where every 1 rupiah/dollar weakening of the rupiah causes a decrease in stock price of 0.270 rupiah. Simultaneously, both variables have a significant effect with a calculated F-value of 19.310 > F-table 4.74 and significance of 0.001 < 0.05, and an R-square value of 0.847, explaining 84.7%. This means that the inflation and Bank Indonesia's exchange rate variables are able to explain 84.7% of the variability in PT Goodyear Indonesia Tbk's stock price, while the remaining 12.3% is explained by other factors not examined in this study. This research provides valuable contributions for investors in making investment decisions and for company management in developing macroeconomic risk mitigation strategies.